In my mother's house - Clark, Ann Nolan; Herrera, Velino (New York Puffin Books, 1992)
A young Tewa Indian describes the homes, customs, work, and strong communal spirit of his people.
"First published May 1941."
Keywords: Tewa Indians -- Juvenile poetry; Children's poetry, American; Tewa Indians -- Poetry; Indians of North America -- Poetry; American poetry